The Existence of Islamic Education Towards Moral Development in the 5.0 Era - Erwin (ETDC: Indonesian Journal of Research and Educational Review, 2023)
This article discusses the existence of Islamic education towards moral development in the 5.0 era, which necessitates the existence of Islamic education to prevent moral degradation in society. For this reason, Islamic religious education is a necessity for cultivating the spiritual potential of every individual. The purpose of this article is to maintain the existence of Islamic religious education for moral development in the 5.0 era. The research results show that education is a conscious and planned effort to foster the spiritual needs of each individual in the 5.0 era. Likewise, Islamic education shapes individual morals through formal, informal, and non-formal education programs.